Cranial suture closure as an age indicator: A review. (February 2020) - Ruengdit, Sittiporn; Troy Case, D.; Mahakkanukrauh, Pasuk
Highlights: The study provides a review of cranial suture closure as an age indicator. Cranial suture closure has potential as a useful indicator for age estimation. Data and imaging analysis improve efficiency of suture closure as age indicator. Abstract: Cranial suture closure has been recognized for over a century as a useful trait for age estimation. Although this indicator has become a standard feature of age assessment protocols in skeletal remains, serious questions have been raised about its reliability. This article attempts to provide a comprehensive review of cranial suture closure as an age indicator from several perspectives, including its anatomy and history, as well as issues relating to validation, statistics, and the potential of technological advancements to improve outcomes. We further suggest a path forward for the use of cranial suture closure as an estimator of age. Although its unreliability has been widely reported, cranial suture closure still appears to have value as an aging method, and it is hoped that the information contained in this article can serve as a stepping stone toward more effective use of this indicator. The cranium is often more durable than other skeletal elements in both archaeological and forensic circumstances, so maximizing the effectiveness of cranial indicators is an important goal. It is hoped that recent advancements in technology and in analytical approaches to the cranial sutures could breathe some new life into this feature as an indicator of age.